PENDAPAT TEOLOGIS MEMBAWA JENAZAH ANGGOTA GEREJA MASEHI ADVENT HARI KETUJUH KE GEREJA - Milton T. Pardosi (Fakultas Filsafat Universitas Advent Indonesia, 2013)
Bringing the corpse of a member of Seventh-day Adventist Church to the church before burial ceremony has been a discussion among members of the church itself. Some agree but others not. Those who agreeare divided into two groups based on criteria established by each congregation. The activityto bring the corpse to the church before burial ceremony does not have a theological basis in the Bible and Spirit of Prophecy. Moreover, they also do not provide provisions relating to it as well as positive or negative impact if the body is brought to the church or not. Therefore, the organization of Seventh-day Adventists Church should give clear guidance to the criteria that needs to be followed by all churches under Seventh-day Adventists organization to occur alignment in addressing this issue. When it turns out that decision being handed out to each congregation, then, let these three important things need to be considered, namely: (1) the person who died must be a faithful member of the Seventh-day Adventists Church. This is evidenced by a baptist certificate or a statement from the family or Seventh-day Adventists Church that requests, or membership record; (2) the person diesin a reasonble state (not suicide, drug addicts, etc.); (3) the corpse that can be brought to the church is not just limited to the pastor, church elder, church founders, old people, but to the younger age group also should be given the opportunity.